2008
DOI: 10.1121/1.2832317
|View full text |Cite
|
Sign up to set email alerts
|

In vivo ultrasonic attenuation slope estimates for detecting cervical ripening in rats: Preliminary results

Abstract: To effectively postpone preterm birth, cervical ripening needs to be detected and delayed. As the cervix ripens, the spacing between the collagen fibers increases and fills with water, hyaluronan, decorin, and enzymes suggesting that the ultrasonic attenuation of the cervix should decrease. The decrease in ultrasonic attenuation may be detectable, leading to an effective means of detecting cervical ripening. Herein, the traditional attenuation slope-estimation algorithm based on measuring the downshift in cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 27 publications
(31 reference statements)
2
52
0
Order By: Relevance
“…We can rewrite equation The size of the ROI was varied in both the axial and lateral direction. Our previous studies have shown that approximately 15 pulse lengths in the axial direction and 15 pulse lengths in the axial direction and 15 echoes in the lateral direction gave a standard deviation on the order of 25% in the attenuation estimates for simulations, phantom experiments, and in the rat cervix when using the spectral log difference algorithm, while the spectral difference algorithm had a standard deviation of less than 13% for the same ROI size [9,37,39].The pulse length was calculated by taking the auto correlation coefficient of time samples from RF echo lines of the phantom data. Samples with absolute correlation coefficient greater than 0.2 were considered correlated and determined the time pulse length.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We can rewrite equation The size of the ROI was varied in both the axial and lateral direction. Our previous studies have shown that approximately 15 pulse lengths in the axial direction and 15 pulse lengths in the axial direction and 15 echoes in the lateral direction gave a standard deviation on the order of 25% in the attenuation estimates for simulations, phantom experiments, and in the rat cervix when using the spectral log difference algorithm, while the spectral difference algorithm had a standard deviation of less than 13% for the same ROI size [9,37,39].The pulse length was calculated by taking the auto correlation coefficient of time samples from RF echo lines of the phantom data. Samples with absolute correlation coefficient greater than 0.2 were considered correlated and determined the time pulse length.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that as the delivery time approaches, the collagen rich cervix is filled with water and enzymes which results in a lower attenuation value and a softening of the cervix. Our earlier work showed that attenuation of the cervix decreased as the cervix prepared for delivery [8][9][10][11][12]. The softening of the cervix can also be quantified using shear wave elastography [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been also reported that the attenuation coefficient differs for cancerous and healthy tissue (Saijo, Sasaki, 1996). Moreover, the noninvasive determination of ultrasonic attenuation enables to predict the premature delivery in rats and humans (Bigelow et al, 2008;McFarlin et al, 2010). These reports motivate us to search for efficient methods of unambiguous attenuation estimation to be used in ultrasonic (US) imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Saijo and Sasaki (1996) employed scanning acoustic microscope to measure five types of gastric cancer and indicated different attenuation coefficients and sound speeds comparing to normal tissue. Bigelow et al (2008) investigated possibility of prediction of the premature delivery based on the noninvasive ultrasonic attenuation determination. In many other publications it has been reported that pathological processes can lead to changes in the mean attenuation coefficient that range from several percent for cirrhotic human liver, through dozens percent for fatty human liver (Lu et al, 1999), or degenerated bovine articular cartilage (Nieminen et al, 2004) to over a hundred percent in case of porcine liver HIFU treatment in vivo (Zderic et al, 2004) or two hundred percent for porcine kidney thermal coagulation (Worthington, Sherar, 2001).…”
Section: Introductionmentioning
confidence: 99%